How long and how much? Learning about the design of wage subsidies from policy discontinuities - Anna Sjögren; Johan Vikström (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
Employment and wage subsidies are used to combat long-term unemployment, yet there is little research to guide the design of such programs. Discontinuities in the design and implementation of wage subsidies under the Swedish New Start Jobs-policy allow us to study effects of both subsidy rate and subsidy duration. We find that doubling of the subsidy rate has a substantial impact on job finding rates but that doubled subsidy duration has no such effect. We find the opposite pattern when we study the effects on the probability of staying employed for those who find subsidized employment. Interestingly, the positive employment effect of doubling the subsidy duration persists after the expiry of the employment subsidies.
Keywords: J08; J64; J68; 330; Wage-subsidies; subsidy duration; duration; subsidy rate; policy design; long-term unemployment